2023
DOI: 10.1371/journal.pntd.0011062
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchis sinensis aggravates biliary fibrosis through promoting IL-6 production via toll-like receptor 2-mediated AKT and p38 signal pathways

Abstract: Clonorchis sinensis is an important food-borne zoonotic parasite which has been linked to biliary fibrosis and cholangiocarcinoma. However, the details of the pathogenesis of C. sinensis were unclear. To explore the role and regulatory mechanism of toll-like receptor 2 (TLR2) in C. sinensis-induced biliary fibrosis, we established the C. sinensis-infected C57BL/6 mouse model with TLR2-/- and wild type (WT) mice. The mortality rate, liver lesions, TLR2 and TGF-β1 expression, phosphorylation of Smad2/3, AKT, p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The disease is widespread in China, South Korea and Vietnam, affecting an estimated 15 to 20 million people [35]. Clonorchis sinensis infection can trigger hepatic in ammation, which can ultimately lead to cholangitis, periductal hepatic brosis, liver cirrhosis, and even cholangiocarcinoma [4][5][6][7]. Although there are existing anti-helminthic drugs for treating Clonorchis sinensis infection (such as praziquantel and tribendimidine), side effects have been reported during tribendimidine treatment and the overuse of these drugs could lead to drug resistance [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is widespread in China, South Korea and Vietnam, affecting an estimated 15 to 20 million people [35]. Clonorchis sinensis infection can trigger hepatic in ammation, which can ultimately lead to cholangitis, periductal hepatic brosis, liver cirrhosis, and even cholangiocarcinoma [4][5][6][7]. Although there are existing anti-helminthic drugs for treating Clonorchis sinensis infection (such as praziquantel and tribendimidine), side effects have been reported during tribendimidine treatment and the overuse of these drugs could lead to drug resistance [36].…”
Section: Discussionmentioning
confidence: 99%
“…During acute severe infection, there may be in ammatory changes such as immune cell in ltration and activation around the bile ducts and in the liver tissues [4]. Chronic infection can induce hepatic damages, steatosis and brosis, which can also contribute to the development of cholangiocarcinoma and hepatocellular carcinoma [5][6][7][8]. Clonorchiasis is also related to necrotizing hepatitis, in which immature liver ukes migrate and release toxins to damage the hepatocytes and lead to necrotic cell death [9].…”
Section: Introductionmentioning
confidence: 99%
“…sinensis , and the immune response of BECs TLRs play the important role during C . sinensis infection [ 9 , 24 ]. We used CsEVs and BECs to simulate the interaction process between C .…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6 and TNF secreted by BECs and macrophages are the vital cytokines in C . sinensis induced liver injure and fibrosis [ 15 , 24 ]. The present data indicated that BECs TLR3 deficiency resulted in significantly increased IL-6 and TNF secretion induced by CsEVs, which may be an important reason for more severe liver damage and liver fibrosis in TLR3 -/- mice infected with C .…”
Section: Discussionmentioning
confidence: 99%